AVALIAÇÃO DAS ALTERAÇÕES DENTOESQUELÉTICAS DECORRENTES DO TRATAMENTO DA MALOCLUSÃO DE CLASSE II COM O APARELHO FORSUS POR MEIO DE TOMOGRAFIA COMPUTADORIZADA - Sakuno, Antonio Carlos (2011)
This study aimed to evaluate cephalometrically, by means of Cone Beam Computed Tomography (CBCT), the dentoalveolar and skeletal effects of Class II correction ith the Forsus® appliance. Study group was composed by 10 patients, 7 males and 3 females, with initial mean age of 16,1 years, with at least ½ Class II, minimum overjet of 5mm, no supernumeraries, anodontia or permanent teeth loss. Facial pattern should be meso or brachyfacial. Patients were evaluated and it was shown they were at stage IV or V of bone maturation, seen by cervical vertebrae. Forsus utilization period was 7,16 years on average, with a CBCT (T1) before and another one (T2) after the removal of Forsus. Paired t-test was used for statistical analysis. Results showed a decrease of SNA and a small grown of mandible, what improved maxillomandibular relationship; there was a counter-clockwise mandibular rotation and a clockwise rotation of the occlusal plane. Upper incisors were retruded, retroclined and extruded, and upper molars showed distal angulation. Lower incisors were proclined and intruded, and lower molars were mesialized and extruded. So, Forsus appliance showed to be effective in Class II correction, proportioning more dentoalveolar alterations than skeletal changes.